2019
DOI: 10.1002/joc.6357
|View full text |Cite
|
Sign up to set email alerts
|

Skill and uncertainty in surface wind fields from general circulation models: Intercomparison of bias between AGCM, AOGCM and ESM global simulations

Abstract: Understanding the reliability of global climate models (GCMs) to reproduce the historical surface wind fields is integral part of building robust projections of surface wind‐climate, and other wind‐dependent geophysical climatic variables. Understanding the skill of atmosphere‐only models (AGCM), coupled atmosphere–ocean models (AOGCM) and fully coupled earth system models (ESM) is likewise paramount to assess any systematic model improvements. In this paper, we systematically assess whether surface wind field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Despite being a unique database for ocean wave climate research, it only simulates one realization given the same climatological forcing. In terms of the driving wind fields, Morim et al (2020) found that the underlying physics of the atmospheric component of climate models is the dominant source of bias in simulated wind fields, and that inter-model uncertainty is typically 2-4 times larger than the uncertainty associated with internal variability. However, they used a relatively small sample (3-10 model realizations).…”
Section: Introductionmentioning
confidence: 99%
“…Despite being a unique database for ocean wave climate research, it only simulates one realization given the same climatological forcing. In terms of the driving wind fields, Morim et al (2020) found that the underlying physics of the atmospheric component of climate models is the dominant source of bias in simulated wind fields, and that inter-model uncertainty is typically 2-4 times larger than the uncertainty associated with internal variability. However, they used a relatively small sample (3-10 model realizations).…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the IPCC and other climate scientists have progressed to implement and develop the Coupled Model Intercomparison Project (CMIP) with the latest being CMIP6 [ 160 ]. In CMIP6, various ensembles of GCMs have been run collectively and results compared in an attempt to understand how the global climate will respond to future scenarios of increasing/decreasing anthropogenic radiative forcing relative to present‐day climate conditions [ 157 , 161 , 162 ]. For example, Andrews et al [ 163 ] recently ran simulations using the HadGEM3-GC3.1 for CMIP6, testing climatic responses to historical forcings such as solar irradiance, ozone concentrations, greenhouse gases, land‐use changes, and aerosols compared results to observational data.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have evaluated GCMs performance by various approaches, such as employing a grid of measured data (e.g., Zha et al ., 2020) or reanalysis datasets (e.g., Morim et al ., 2020). In the latter approach, the performance of the reanalysis datasets should be first assessed (Morim et al ., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have evaluated GCMs performance by various approaches, such as employing a grid of measured data (e.g., Zha et al, 2020) or reanalysis datasets (e.g., Morim et al, 2020). In the latter approach, the performance of the reanalysis datasets should be first assessed F I G U R E 3 Accumulated monthly frequency of TCs over the AS within 1891-2020 (adopted from IMD, 2019) [Colour figure can be viewed at wileyonlinelibrary.com] (Morim et al, 2018).…”
Section: Reanalysis Datasetsmentioning
confidence: 99%